Digital Transformation Strategy Model To Improve The Competitiveness Of Msmes: A Systematic Literature Review-Based Analysis - Fitriadi, Agus; Sudarmiatin; Agus Hermawan (International Journal of Technology and Education Research, 2025)
This study aims to analyze digital transformation strategy models for enhancing corporate competitiveness, focusing on MSMEs in Indonesia. Using a Systematic Literature Review (SLR) method combined with bibliometric analysis, this study analyzed 67 articles published between 2018 and 2024 from the Scopus and Web of Science databases. The results reveal that an effective digital transformation strategy is multidimensional, synergistically integrating aspects of technology, human resources, business strategy, and organizational culture. The bibliometric analysis identified three main research clusters: the impact of the COVID-19 pandemic on digital acceleration, the specific context of Indonesian MSMEs, and the relationship between digital transformation and performance and strategic roles. Key findings indicate that successful digital transformation depends not only on technology adoption but also on the ability to build dynamic capabilities, digital leadership, and cultural adaptation. This research contributes to the development of an integrative model that integrates sustainability, resilience, and local wisdom in the digital transformation strategy of Indonesian MSMEs, while also identifying research gaps for further study.